Ferrocene metal phthalocyanine-metal complex / ceramic composite wave-shrinking base material and preparation method thereof

By using ferrocene metal phthalocyanine-metal complex and ceramic composite materials and combined with γ irradiation treatment, the problem of antennas being difficult to miniaturize and broadband in the frequency band below 2GHz in the prior art is solved, and efficient miniaturize and broadband antenna design in the frequency band 0.1 to 10.0GHz is achieved.

CN119581871APending Publication Date: 2025-03-07SHANGHAI MICROWAVE EQUIP RES INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411641473.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to achieve miniaturization and broadband antennas in frequency bands below 2GHz, and the antennas designed with conventional dielectric substrates are mostly narrowband, which limits their applications in broadband radar, communications and electronic confrontation.

Method used

The ferrocene metal phthalocyanine-metal complex/ceramic composite shrinkage substrate is used to form a composite material with high dielectric properties by synthesizing the Fe, Co, Ni, Mn, Cr ion-coordinated ferrocene metal phthalocyanine-metal complex containing Fe, Co, Ni, and Ni with nano-scale dielectric ceramic powder, thermoset engineering plastics or thermoplastic resins, flame retardants and surface modifiers, and the material performance is improved by Co60-γ irradiation treatment.

Benefits of technology

In the wide frequency band of 0.1 to 10.0GHz, the antenna is miniaturized and broadened, while maintaining high gain performance, simplifying structural design, and improving the overall performance of the antenna.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005138575370000031
    Figure BDA0005138575370000031
  • Figure BDA0005138575370000051
    Figure BDA0005138575370000051
  • Figure BDA0005138575370000071
    Figure BDA0005138575370000071
Patent Text Reader

Abstract

The invention provides a ferrocene metal phthalocyanine-metal complex / ceramic composite wave-shrinking base material and a preparation method of the ferrocene metal phthalocyanine-metal complex / ceramic composite wave-shrinking base material. The ferrocene metal phthalocyanine-metal complex / ceramic composite wave-shrinking base material is characterized by comprising the following raw materials in parts by mass: a component A: 20-40 parts of a ferrocene metal phthalocyanine-metal complex organic magnet which is coordinated by any one of Cu, Co, Ni, Mn and Cr ions and contains Fe, Co and Ni; the component B is prepared from 20 to 50 parts of nano-scale dielectric ceramic powder; a component C: 10-20 parts of a thermosetting engineering plastic prepolymer or thermoplastic resin; a component D: 0.5 to 3.0 parts of a flame retardant; and the component E comprises 0.5-2.0 parts of a surface modifier, and the dose of the surface modifier subjected to Co < 60 >-gamma irradiation is 0-300 KGy. The base material disclosed by the invention can be used for realizing miniaturization and broadband of an antenna by using the simplest structural design in a wide frequency band of 0.1-10.0 GHz.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite wave shrinkage substrate, in particular to a ferrocene metal phthalocyanine-metal complex / ceramic composite wave shrinkage substrate and a preparation method thereof. Background Art

[0002] Modern warfare and national economic development require that electronic equipment such as communications, radar, navigation, and electronic countermeasures have multifunctional, miniaturized, and highly maneuverable performance. In order to meet this need, electronic technology is developing in the direction of lightweight, miniaturization, and planarization, that is, light, small, and thin. r ) and relative dielectric constant (ε' r ) In dielectric materials, the wavelength of electromagnetic waves is The multiple is reduced, where Therefore, to reduce the geometric size of electronic devices or antennas, the F value should be large, that is, ε' r and μ' r Should be as large as possible.

[0003] At present, microstrip components, microstrip circuits and networks made of dielectric substrates have been widely used in radar, communication navigation, electronic countermeasures and other fields at home and abroad, but most of them are in high frequency bands, that is, in the range of 2 to 35 GHz; and for applications in the frequency band below 2 GHz, it is difficult to miniaturize them due to their large size; in addition, antennas designed and made using conventional dielectric substrates are mostly narrow-band, which limits its application in broadband radar, communication, electronic countermeasures and other fields.

[0004] Antennas are key components at the front end of communication systems, especially miniaturization of dielectric antennas with excellent performance. Miniaturization should also have the overall performance of the antenna (gain, efficiency, bandwidth), which is a very challenging scientific research project. Over the years, domestic and foreign scholars have studied various methods to achieve miniaturization of electrically small antennas. Most of them use methods such as loading anisotropic dielectrics in the near field of the antenna, adding active networks, using dielectric substrates with high dielectric constants or fractal structures, etc., which can effectively achieve the miniaturization of antennas. However, it is at the cost of reducing a certain indicator, so it is difficult to obtain a miniaturized antenna with perfect performance.

[0005] So far, there are many reports on ferrocene and metal phthalocyanine compounds, but there are few studies on the electromagnetic properties of ferrocene metal phthalocyanine. Only Deng Ke et al. reported on the synthesis and characterization of phthalocyanine ferrocene type high-resolution microwave absorbing materials: Journal of Sichuan Normal University (Natural Science Edition), 2007, 30 (3), 369: Study on the microwave dielectric properties of phthalocyanine modified polydivinyl ferrocene (Chemical Research and Application, 2007, 19 (5) 494: and Deng Ke's master's thesis; Molecular design, synthesis and performance research of polymerized ferrocene microwave absorbing materials, 2007 (Sichuan Normal University): It studies the microwave absorbing properties of ferrocene phthalocyanine type magnetic polymers. Invention patent literature Publication No. CN101328193A reports ferrocene face-to-face bisphthalocyanine complexes and their uses, which are mainly used as catalysts for redox reactions; invention patent ZL200910167623.7 (inventors: Lin Yun, Lin Zhanru) reports composite materials containing ferrocene phthalocyanine metal organic magnets and preparation methods. Although they are also suitable for miniaturization of high-frequency electronic devices and antennas, the reaction conditions for synthesizing high molecular weight ferrocene phthalocyanine magnets are difficult to control, the electromagnetic consistency of the magnets is poor, and the yield is also low, so it is difficult to achieve industrialization. Summary of the invention

[0006] The purpose of the present invention is to solve the defects of the above-mentioned prior art and provide a ferrocene metal phthalocyanine-metal complex / ceramic composite wave shrinking substrate and its preparation method, which can realize the miniaturization and broadband of the antenna with the simplest structural design in a wide frequency band of 0.1 to 10.0 GHz.

[0007] The present invention provides a ferrocene metal phthalocyanine-metal complex / ceramic composite wave shrinkage substrate, characterized in that the raw materials thereof include, by weight:

[0008] Component A: 20-40 parts of ferrocene metal phthalocyanine-metal complex organic magnet containing Fe, Co, Ni coordinated by any one of Cu, Co, Ni, Mn, Cr ions;

[0009] Component B: nanometer-level dielectric ceramic powder: 20 to 50 parts;

[0010] Component C: thermosetting engineering plastic prepolymer or thermoplastic resin: 10-20 parts;

[0011] Component D: flame retardant: 0.5-3.0 parts;

[0012] Component E: surface modifier: 0.5-2.0 parts,

[0013] And experienced Co 60 -γ irradiation dose is 0~300KGy.

[0014] Furthermore, the structural formula of component A is:

[0015]

[0016] Wherein M1 is any one of Fe, Co and Ni;

[0017] R is methylene (CH2) n , n = 0, 1, 2, or 3;

[0018] M2 is any one of chlorides, sulfates, acetates or nitrates of divalent metal ions Cu, Co, Ni, Mn or Cr.

[0019] Furthermore, the component B is any one or more of the rutile ceramic series in nano-scale high-frequency dielectric ceramics or the BaO-TiO2 ceramic series in nano-scale microwave dielectric ceramics.

[0020] Furthermore, the rutile ceramic series includes rutile titanium dioxide, calcium titanate, strontium titanate and zirconium titanate ceramic powders. The dielectric constant of rutile titanium dioxide is 80-10, the dielectric constant of calcium titanate is 150-200, the dielectric constant of strontium titanate is 250-350, and the dielectric constant of zirconium titanate is 60; the dielectric constant of the BaO-TiO2 series ceramics is 600-800, and the particle size of the high-frequency dielectric ceramics and microwave dielectric ceramics is 50-300nm.

[0021] Furthermore, the component C is any one or more selected from the prepolymers of cyanate resin, polyphenylene ether ketone, polyphenylene sulfide, bismaleimide resin as thermosetting engineering plastics, and polyolefin, polyurethane, polyether, and polycarbonate as thermoplastic resins.

[0022] Furthermore, the component D is any one selected from decabromodiphenyl ether, melamine, polyphosphate melamine, aromatic phosphites, diphosphites, phosphonates, and phosphates.

[0023] Furthermore, the component E is any one selected from titanate coupling agent, silica coupling agent, aluminate coupling agent, cationic or anionic surfactant, dimethylsiloxane or dimethylsiloxane copolymer; or any one of organic modified polysiloxane, ureapropyl triethoxysilane, vinyl methyl dimethylsiloxane; or any one of oleic acid, acrylic acid and oleic acid in a 1:1 mixture.

[0024] Furthermore, the component A is obtained by the following synthesis reaction:

[0025]

[0026] Wherein M1 is any one of Fe, Co and Ni;

[0027] Lewis acid is any one of BF3, AlCl3, NbCl5 or CF3NaSO3;

[0028] R is methylene (CH2) n , n = 0, 1, 2, or 3;

[0029] M2 is any one of chlorides, sulfates, acetates or nitrates of divalent metal ions Cu, Co, Ni, Mn or Cr.

[0030] Furthermore, in the synthesis reaction, the molar ratio of ferrocenylalkylamide to metal phthalocyanine dicarbonyl chloride is (2.5-3.0):1.0, and the Lewis acid is any one of BF3, AlCl3, NbCl5 or CF3NaSO3.

[0031] The present invention also provides a method for preparing the above-mentioned ferrocene metal phthalocyanine-metal complex / ceramic composite wave shrinkage substrate, which is characterized by comprising the following steps:

[0032] Step 1: first add anhydrous ethanol at 50-60° C. to the surface modifier, i.e. component E, to obtain an ethanol solution of the surface modifier;

[0033] Step 2: Soak the ferrocene metal phthalocyanine-metal complex organic magnet, i.e. component A, the nano-scale dielectric ceramic powder, i.e. component B, and the flame retardant, i.e. component D, in the ethanol solution of the surface modifier for 30 minutes, filter the solution, wash away the residual ethanol on the surface modifier with acetone, and then dry the solution;

[0034] Step 3: After fully mixing component A, component B, component D and component E under a high-speed stirrer, kneading with thermosetting engineering plastic prepolymer or thermoplastic resin, namely component C, in an open mill for 30 to 40 minutes under a certain temperature condition, and hot pressing or extruding into substrates of various specifications according to technical requirements, wherein the certain temperature refers to 130 to 150° C. for thermoplastic resin and 50 to 70° C. for thermosetting engineering resin prepolymer;

[0035] Finally, use Co 60 -γ irradiation dose is 0~300KGy.

[0036] In summary, the present invention provides a magnetic medium (μ r ) and dielectric (ε r ) The functional materials with material characteristics are suitable for a wide frequency band of 0.1 to 10.0 GHz. While ensuring high gain, the simplest structural design can be used to achieve miniaturization and broadband antennas. DETAILED DESCRIPTION

[0037] The above contents of the present invention are further described in detail below through the specific implementation methods of the embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. Various substitutions or changes made according to common technical knowledge and customary means in the art without departing from the above technical concept of the present invention should be included in the scope of the present invention.

[0038] The ferrocene metal phthalocyanine-metal complex / ceramic composite wave shrinking substrate and its preparation method are ferrocene metal phthalocyanine-metal complex organic magnet and high-frequency or microwave dielectric ceramic organic magnetic composite wave shrinking substrate and its preparation method.

[0039] The raw materials of the ferrocene metal phthalocyanine-metal complex / ceramic composite wave shrinkage substrate of the present invention include, by weight:

[0040] Component A: 20-40 parts of ferrocene metal phthalocyanine-metal complex organic magnet containing Fe, Co, Ni coordinated by any one of Cu, Co, Ni, Mn, Cr ions;

[0041] Component B: nanometer-level dielectric ceramic powder: 20 to 50 parts;

[0042] Component C: thermosetting engineering plastic prepolymer or thermoplastic resin: 10-20 parts;

[0043] Component D: flame retardant: 0.5-3.0 parts;

[0044] Component E: surface modifier: 0.5 to 2.0 parts.

[0045] And experienced Co 60 -γ irradiation dose is 0~300KGy.

[0046] Component A:

[0047] The organic magnet of ferrocene metal phthalocyanine-metal complex containing Fe, Co, Ni coordinated by any one of Cu, Co, Ni, Mn, Cr ions has the following structural formula:

[0048]

[0049] Wherein M1 is any one of Fe, Co and Ni;

[0050] R is methylene ((CH2) n , n = 0, 1, 2, or 3;

[0051] M2 is any one of chlorides, sulfates, acetates or nitrates of divalent metal ions Cu, Co, Ni, Mn or Cr, preferably acetates or chlorides of Cu, Co or Ni.

[0052] The synthesis reaction of ferrocene metal phthalocyanine-metal complex organic magnet is as follows:

[0053]

[0054] Wherein M1 is any one of Fe, Co and Ni;

[0055] Lewis acid is any one of BF3, AlCl3, NbCl5 or CF3NaSO3;

[0056] R is methylene (CH2) n , n = 0, 1, 2, or 3;

[0057] M2 is any one of chlorides, sulfates, acetates or nitrates of divalent metal ions Cu, Co, Ni, Mn or Cr.

[0058] The molar ratio of ferrocenylalkylamide to metal phthalocyanine dicarbonyl chloride is (2.5-3.0):1.0.

[0059] The amount of Lewis acid used as the catalyst is 1-3% of the weight of ferrocenyl chloride, but preferably 4-6 grams.

[0060] The organic solvent in the reaction is any one selected from n-pentanol, isopentanol, tetrahydrofuran, dioxane, N,N-dimethylformamide, dimethyl sulfoxide, xylene, diethylbenzene, N-methylpyrrolidone, and lutidine, preferably dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone or tetrahydrofuran.

[0061] Component B:

[0062] The nanometer-scale dielectric ceramic powder is selected from rutile titanium dioxide, calcium titanate, strontium titanate and zirconium titanate ceramic powders in the rutile ceramic series of nanometer-scale high-frequency dielectric ceramics, Ba2TiO2 in the BaO-TiO2 series ceramics of nanometer-scale microwave dielectric ceramics, and Ba2TiO 20 、Ba6Ti 17 O 40 、Ba4Ti 12 O 50 , TiO2(Zr:Sn)TiO2 and rare earth ceramics La2Ti2O7, (Zr:Sn)TiO4, BaNd2Ti5O 14 、BaSm2TiO 14 , Nd2Ti2O7, (LiSm)TiO3, Ba(Mg 1 / 3 Ta 2 / 3 )O3、Ba(Zn 1 / 3Ta 2 / 3 )O3、Ba(Zn 1 / 3Nb 2 / 3 )、Sr(Zn 1 / 3 Nb 2 / 3 )O3, preferably rutile titanium dioxide, calcium titanate, Sr(Zn 1 / 3 Nb 2 / 3 ) 30 , or BaSm2TiO 14 .

[0063] In the high-frequency dielectric ceramics, the dielectric constant of rutile titanium dioxide is 80-10, and the optimal value is 90. The dielectric constant of calcium titanate is 150-200, and the optimal value is 180. The dielectric constant of strontium titanate is 250-350, and the optimal value is 280. The dielectric constant of zirconium titanate is 60. In the microwave dielectric ceramics, the dielectric constant of BaO-TiO2 series ceramics is 600-800, and the optimal value is 650. The particle size of the high-frequency dielectric ceramics and microwave dielectric ceramics is 50-300nm, and the optimal value is 80-100nm.

[0064] Component C:

[0065] The thermosetting engineering plastic prepolymer or thermoplastic resin is selected from cyanate resin, polyphenylene ether ketone, polyphenylene sulfide, bismaleimide resin prepolymer as thermosetting engineering plastics, polyolefin, polyurethane, polyether, polycarbonate as thermoplastic resin, any one or more, preferably cyanate resin, bismaleimide resin or polyethylene. For civil products with low application environment temperature requirements, thermoplastic resins with low price and easy addition can be used.

[0066] Component D:

[0067] The flame retardant is any one selected from decabromodiphenyl ether, melamine, polyphosphate melamine, aromatic phosphites, diphosphites, phosphonates and phosphates.

[0068] Component E:

[0069] The surface modifier is selected from titanate coupling agent, silica gel coupling agent, aluminate coupling agent, cationic or anionic surfactant, dimethylsiloxane or dimethylsiloxane copolymer; or any one of organic modified polysiloxane, ureapropyl triethoxysilane, vinyl methyl dimethylsiloxane; or any one of oleic acid, acrylic acid and oleic acid in a 1:1 mixture.

[0070] The method for preparing the ferrocene metal phthalocyanine-metal complex / ceramic composite wave shrinkage substrate as described above comprises the following steps:

[0071] Step 1: first add anhydrous ethanol at 50-60° C. to the surface modifier (component E) to obtain an ethanol solution of the surface modifier.

[0072] Step 2: Soak the ferrocene metal phthalocyanine-metal complex organic magnet (component A) and nanometer-scale dielectric ceramic powder (component B) and flame retardant (component D) in the ethanol solution of the surface modifier for 30 minutes and then filter, wash away the residual ethanol on the surface modifier with acetone, and then dry.

[0073] Step 3: After fully mixing component A, component B, component D and component E under a high-speed stirrer, mix them with thermosetting engineering plastic prepolymer or thermoplastic resin (component C) in an open mill under certain temperature conditions (130-150°C for thermoplastic resin and 50-70°C for thermosetting engineering resin prepolymer) for 30-40 minutes, and hot press or extrude them into substrates (substrates or rods) of various specifications according to technical requirements.

[0074] Finally, according to different technical requirements, Co 60 -γ irradiation dose is 0~300KGy.

[0075] The wave-shrinking substrate of the present invention can realize miniaturization and broadband antenna in a wide frequency band of 0.1 to 10.0 GHz with the simplest structural design.

[0076] Example

[0077] Embodiment 1:

[0078] Preparation of ferrocene phthalocyanine iron-Cu complex organic magnet (component A), the basic operation process of the synthesis is as follows;

[0079] The synthesis steps are as follows: Under the protection of high-purity nitrogen, in a 500ml three-necked flask equipped with a nitrogen inlet and outlet and a dropping funnel, 0.2mmol of phthalocyanine iron dicarbonyl chloride is dissolved in 200ml of tetrahydrofuran (THF) and 5g of AlCl3 is added as a catalyst. Under vigorous stirring, 0.5mmol of ferrocenecarboxamide and 100ml of THF solution are slowly dropped in. After heating and refluxing for 1.5 hours, the precipitate is filtered while hot, and the precipitate is washed with hot ethanol and then washed with acetone. After washing, vacuum drying is carried out, and 0.2 mmol of the intermediate (ferrocenyl phthalocyanine iron) is dissolved in 250 ml of dimethylformamide (TMF), and a solution of 0.4 mmol of the coordination metal salt CuCl2 and 50 ml of TMF is slowly dropped into it: heated to reflux for about 30 minutes under vigorous stirring, and the precipitate is filtered and washed and dried according to the conventional method to obtain a room temperature stable two-dimensional network ferrocenyl phthalocyanine iron-Cu complex organic magnet with a yield of about 75-80% for use.

[0080] Example 2

[0081] First, the ferrocene phthalocyanine iron-Cu complex organic magnet (component A) was synthesized according to Example 1. In the synthesis, except that the solvent was dioxane, the reactants were ferroceneacetamide and phthalocyanine iron dicarbonyl chloride, the catalyst was 5 grams of NbCl5, the coordinated metal salt was cupric acetate, and the intermediate generated in the synthesis was dissolved in dimethyl sulfoxide (DMSO), the remaining operations were the same as in Example 1, and 82% of the room temperature stable two-dimensional network ferrocene phthalocyanine iron-Cu complex organic magnet was obtained for use.

[0082] Then 40 parts of the synthesized organic magnet (component A) were mixed with 35 parts of 100 nm microwave ceramic Ba2TiO 20 The powder (component B), 3 parts of flame retardant decabromodiphenyl ether flame retardant (component D), 2 parts of titanate coupling agent modifier (component E) treated according to step 1 are treated, and after fully mixing components A, B, D and E in a high-speed stirrer (12000prm / min) according to step 3, 20 parts of cyanate resin prepolymer (component C) are mixed in an open mill at 50-60°C for 30-40 minutes, and then hot-pressed into a 120x120x5mm substrate. Finally, irradiation with Co60-γ irradiation dose of 100KGy is performed to obtain a ferrocene phthalocyanine iron-Cu complex magnet / ceramic composite shrink wave substrate.

[0083] The magnetic permeability of the wave-shrinking substrate measured at 200MHz is 3.0, the dielectric constant is 8.5, and the dielectric loss tangent tgδ≤2×10 -3 The copper-clad substrate made of 120×120×5mm can be used to make 100-120MHz VHF antennas with a bandwidth of 15%. In contrast, the antenna made of a similar American Rogers RO3010 dielectric substrate (dielectric constant 10) has a geometric size of 320x320x5mm and a bandwidth of only 5%. Therefore, the performance of the present invention is much better.

[0084] Example 3

[0085] First, ferrocenylphthalocyanine cobalt-Cu complex organic magnet (component A) was synthesized according to Example 1. In the synthesis, except that the solvent was xylene, the coordinating metal salt was copper sulfate, the reactants were ferrocenylpropionamide and cobalt phthalocyanine diformyl chloride, the catalyst was 6 grams of AlCl3, and the intermediate generated in the synthesis was dissolved in lutidine, the remaining operations were the same as in Example 1, and a room temperature stable two-dimensional network ferrocenylphthalocyanine cobalt-Cu complex organic magnet with a yield of 75% was obtained for use.

[0086] Then, 30 parts of the synthesized organic magnet (component A) were treated with 35 parts of 100 nm microwave ceramic BaONd2O3-TiO2 powder (component B), 3 parts of flame retardant phosphate (component D), and 2 parts of aluminate coupling agent modifier (component E) treated according to step 1 according to step 2, and then, after fully mixing components A, B, D and E under a high-speed stirrer (12000prm / min) according to step 3, they were mixed with 20 parts of cyanate resin prepolymer (component C) in an open mill at 50-60°C for 30-40 minutes, and then hot-pressed into a 120x120x5mm substrate, and finally coated with Co 60 -γ irradiation dose was 100KGy to obtain ferrocene phthalocyanine cobalt-Cu / ceramic composite shrink wave substrate.

[0087] The magnetic permeability of the wave-shrinking substrate measured at 300MHz is 3.2, the dielectric constant is 8.0, and the dielectric loss tangent tgδ≤3×10 -3 The copper-clad substrate made of 120×120×5mm can be used to make 120-150MHz VHF antennas with a bandwidth of 13%. In contrast, the antenna made of a similar American Rogers RO3010 dielectric substrate (dielectric constant 10) has a geometric size of 350x350x5mm and a bandwidth of only 6%. Therefore, the performance of the present invention is much better.

[0088] Example 4

[0089] First, a ferrocene phthalocyanine iron-Co complex organic magnet (component A) was synthesized according to Example 1. In the synthesis, except that the solvent was N-methylpyrrolidone, the coordination metal salt cobalt nitrate, the reactants were ferrocenecarboxamide and phthalocyanine iron dicarbonyl chloride, the catalyst was 5 grams of BF3, and the intermediate generated in the synthesis was dissolved in dimethyl sulfoxide (SMSO), the remaining operations were the same as in Example 1, and a room temperature stable two-dimensional network ferrocene phthalocyanine iron-Co complex organic magnet with a yield of 75% was obtained for use.

[0090] Then 40 parts of the synthesized organic magnet (component A) were mixed with 40 parts of 150 nm microwave ceramic Sr (Zn 1 / 3Nb 2 / 3 ) 30 The powder (component B), 1.5 parts of flame retardant phosphonate (component D), and 0.5 parts of dimethylsiloxane surface modifier (component E) treated according to step 1 were treated, and then according to step 3, components A, B, D and E were fully mixed under a high-speed stirrer (12000prm / min), and then mixed with 18 parts of cyanate resin prepolymer (component C) in an open mill at 50-60°C for 30-40 minutes, and then hot-pressed into a 200x200x5mm substrate, and finally coated with Co 60-γ irradiation dose was 200KGy to obtain ferrocene phthalocyanine iron-Co / ceramic composite shrink wave substrate.

[0091] The permeability of the wave-shrinking substrate measured at 300MHz is 3.8, the dielectric constant is 9.5, and the dielectric loss tangent tgδ≤3×10 -3 The copper-clad substrate made of 200×200×5mm can be used to make 50-70MHz VHF antennas with a bandwidth of 15%. In contrast, the antenna made of a similar American Rogers RO 3006 dielectric substrate (dielectric constant 6.15) has a geometric size of 420x420x5mm and a bandwidth of only 5%. Therefore, the performance of the present invention is much better.

[0092] Example 5

[0093] First, ferrocenylphthalocyanine nickel-Mn complex organic magnet (component A) was synthesized according to Example 1. In the synthesis, except that the solvent was N-methylpyrrolidone, the coordinated metal salt manganese acetate, the reactants were ferrocenylpropionamide and nickel phthalocyanine diformyl chloride, the catalyst was 5 g CF3NaSO3, and the intermediate generated in the synthesis was dissolved in dimethylformamide (TMF), the remaining operations were the same as in Example 1, and a room temperature stable two-dimensional network ferrocenylphthalocyanine nickel-Mn complex organic magnet with a yield of 80% was obtained for standby use.

[0094] Then 35 parts of the synthesized organic magnet (component A) were mixed with 40 parts of 300 nm microwave ceramic Sr (Zn 1 / 3Nb 2 / 3 ) 30 The powder (component B), 3 parts of flame retardant decabromodiphenyl ether flame retardant (component D), and 2 parts of surface modifier (component E) made of oleic acid and acrylic acid (1:1) treated according to step 1, and then fully mixed components A, component B, component D and component E under a high-speed stirrer (12000prm / min) according to step 3, and then mixed with 20 parts of bismaleimide resin prepolymer (component C) in an open mill at 130-150°C for 40-50 minutes, and then hot-pressed into a substrate of 200x200x5mm, and finally irradiated with a Co60-γ irradiation dose of 200KGy to obtain a ferrocene phthalocyanine nickel-Co / ceramic composite shrink wave substrate.

[0095] The permeability of the wave-shrinking substrate measured at 300MHz is 3.8, the dielectric constant is 9.5, and the dielectric loss tangent tgδ≤3×10 -3The copper-clad substrate made of 200×200×5mm can be used to make 30-70MHz VHF antennas with a bandwidth of 12%. In contrast, the antenna made of a similar American Rogers RO3010 dielectric substrate (dielectric constant 10) has a geometric size of 320x320x5mm and a bandwidth of only 4%. Therefore, the performance of the present invention is much better.

[0096] Example 6

[0097] First, ferrocenylphthalocyanine nickel-Co complex organic magnet (component A) was synthesized according to Example 1. In the synthesis, except that the solvent was N-methylpyrrolidone, the coordination metal salt cobalt acetate, the reactants were ferrocenylpropionamide and nickel phthalocyanine diformyl chloride, the catalyst was 6 grams of AlCl3, and the intermediate generated in the synthesis was dissolved in dimethyl sulfoxide (SMSO), the remaining operations were the same as in Example 1, and a room temperature stable two-dimensional network ferrocenylphthalocyanine nickel-Co complex organic magnet with a yield of 75% was obtained for use.

[0098] Then, 25 parts of the synthesized organic magnet (component A) are treated with 30 parts of 100nm high-frequency rutile titanium dioxide ceramic powder (component B), 3 parts of flame retardant decabromodiphenyl ether flame retardant (component D), and 2 parts of dimethylsiloxane surface modifier (component E) treated according to step 1 according to step 2, and then, according to step 3, components A, B, D and E are fully mixed under a high-speed stirrer (12000prm / min), and then mixed with 40 parts of bismaleimide resin prepolymer (component C) in an open mill at 130-150°C for 40-50 minutes, and then hot-pressed into a 200x200x5mm substrate, and finally coated with Co 60 -γ irradiation dose was 200KGy to obtain ferrocene phthalocyanine iron-Co / ceramic composite shrink wave substrate.

[0099] The permeability of the wave-shrinking substrate measured at 2.0 GHz is 3.5, the dielectric constant is 10.5, and the dielectric loss tangent tgδ is ≤3×10 -3 The copper-clad substrate made of 200×200×5mm can be used to make antennas with a frequency of 1.0-1.8GHz and a bandwidth of 15%. In contrast, antennas made of a similar American Rogers RO3010 dielectric substrate (dielectric constant 10) have a geometric size of 420x420x5mm and a bandwidth of only 5%. Therefore, the performance of the present invention is much better.

[0100] Example 7

[0101] First, according to Example 1, a ferrocene phthalocyanine iron-Cr complex organic magnet (component A) is synthesized. In the synthesis, except that the solvent is tetrahydrofuran (THF), the coordinated metal salt chromium chloride reactants are ferrocene propionyl chloride and phthalocyanine iron diformyl chloride, the catalyst is 6 grams of BF3, and the intermediate generated in the synthesis is dissolved in xylene, the remaining operations are the same as in Example 1, and a room temperature stable two-dimensional network ferrocene phthalocyanine iron-Cr complex organic magnet with a yield of 78% is obtained for standby use.

[0102] Then, 20 parts of the synthesized organic magnet (component A) are treated with 40 parts of 100nm high-frequency calcium titanate ceramic powder (component B), 1.5 parts of flame retardant decabromodiphenyl ether flame retardant (component D), and 0.5 parts of dimethylsiloxane surface modifier (component E) treated in step 1 according to step 2, and then, according to step 3, components A, B, D and E are fully mixed under a high-speed stirrer (12000prm / min), and then mixed with 38 parts of polyphenylene ether ketone resin prepolymer (component C) in an open mill at 60-70°C for 40-50 minutes, and then hot-pressed into a 200x200x5mm substrate, and finally coated with Co 60 -γ irradiation dose of 100KGy was carried out to obtain ferrocene phthalocyanine iron-Cr / ceramic composite shrink wave substrate.

[0103] The magnetic permeability of the wave-shrinking substrate measured at 3.0 GHz is 3.0, the dielectric constant is 12.5, and the dielectric loss tangent tgδ≤3×10 -3 The copper-clad substrate made of 200×200×5mm can be used to make antennas with a frequency of 2.0-3.0GHz and a bandwidth of 15%. In contrast, antennas made of a similar American Rogers RO3010 dielectric substrate (dielectric constant 10) have a geometric size of 420x420x5mm and a bandwidth of only 6%. Therefore, the performance of the present invention is much better.

[0104] Example 8

[0105] First, a ferrocene phthalocyanine iron-Mn complex organic magnet (component A) was synthesized according to Example 1. In the synthesis, except that the solvent was dioxane, the coordinated metal salt manganese chloride, the reactants were ferroceneacetamide and phthalocyanine iron dicarbonyl chloride, the catalyst was 5 grams of NbCl5, and the intermediate generated in the synthesis was dissolved in dimethylformamide (TMF), the remaining operations were the same as in Example 1, and a room temperature stable two-dimensional network ferrocene phthalocyanine iron-Mn complex organic magnet with a yield of 77% was obtained for use.

[0106] Then, 20 parts of the synthesized organic magnet (component A) were treated with 35 parts of 100nm high-frequency calcium titanate ceramic powder (component B), 0.5 parts of flame retardant polyphosphate melamine (component D), and 1.5 parts of titanate coupling agent surface modifier (component E) treated in step 1 according to step 2, and then, according to step 3, components A, B, D and E were fully mixed under a high-speed stirrer (12000prm / min), and then mixed with 42 parts of polyphenylene ether ketone resin prepolymer (component C) in an open mill at 60-70°C for 40-50 minutes, and then hot-pressed into a 200x200x5mm substrate, and finally coated with Co 60 -γ irradiation dose was 100KGy to obtain ferrocene phthalocyanine iron-Mn / ceramic composite shrink wave substrate.

[0107] The magnetic permeability of the wave-shrinking substrate measured at 10.0 GHz is 2.0., the dielectric constant is 12.5, and the dielectric loss tangent tgδ≤3×10 -3 The copper-clad substrate made of 100×100×5mm can be used to make antennas with a frequency of 5.0-8.0GHz and a bandwidth of 12%. In contrast, antennas made of a similar American Rogers RO3010 dielectric substrate (dielectric constant 10) have a geometric size of 250x250x5mm and a bandwidth of only 4%. Therefore, the performance of the present invention is much better.

[0108] Example 9

[0109] First, synthesize ferrocene phthalocyanine iron-Cr complex organic magnet (component A) according to Example 1. In the synthesis, except that the solvent is dimethyl sulfoxide (SMSO), the coordination metal salt chromium sulfate, the reactants are ferrocenecarboxamide and phthalocyanine iron dicarbonyl chloride, the catalyst is 5 grams of CF3NaSO3, and the intermediate generated in the synthesis is dissolved in lutidine, the remaining operations are the same as in Example 1, and a room temperature stable two-dimensional network ferrocene phthalocyanine iron-Cr complex organic magnet with a yield of 75% is obtained for use.

[0110] Then 10 parts of the synthesized organic magnet (component A) were mixed with 50 parts of 100 nm BaSm2TiO 14 The ceramic powder (component B), 1.5 parts of flame retardant polyphosphate melamine (component D), and 0.5 parts of oleic acid surface modifier (component E) treated according to step 1 are treated, and then according to step 3, components A, component B, component D and component E are fully mixed under a high-speed stirrer (12000prm / min), and then mixed with 38 parts of polyphenylene ether ketone resin prepolymer (component C) in an open mill at 60-70°C for 40-50 minutes, and then hot-pressed into a substrate of 100x100x5mm, without Co60-γ irradiation, a ferrocene phthalocyanine iron-Cr / ceramic composite shrink wave substrate can be obtained.

[0111] The magnetic permeability of the wave-shrinking substrate measured at 10.0 GHz is 2.2, the dielectric constant is 13.5, and the dielectric loss tangent tgδ is ≤2.5×10 -3 The copper-clad substrate made of 80×80×4mm can be used to make antennas with a frequency of 8.0-10.0GHz and a bandwidth of 15%. In contrast, antennas made of a similar American Rogers RO3010 dielectric substrate (dielectric constant 10) have a geometric size of 200x200x4mm and a bandwidth of only 5%. Therefore, the performance of the present invention is much better.

[0112] Example 10

[0113] First, ferrocene phthalocyanine cobalt-Ni complex organic magnet (component A) was synthesized according to Example 1. In the synthesis, except that the solvent was dioxane, the coordinated metal salt nickel acetate, the reactants were ferrocenecarboxamide and cobalt phthalocyanine dicarbonyl chloride, the catalyst was 5 grams of NbCl5, and the intermediate generated in the synthesis was dissolved in lutidine, the remaining operations were the same as in Example 1, and a room temperature stable two-dimensional network ferrocene phthalocyanine cobalt-Ni complex organic magnet with a yield of 82% was obtained for use.

[0114] Then 20 parts of the synthesized organic magnet (component A) were mixed with 50 parts of 100 nm BaSm2TiO 14 Ceramic powder (component B), 3.0 parts of flame retardant polyphosphate melamine (component D), 2.0 parts of titanate coupling agent (component E) treated according to step 1, and then fully mixed components A, B, D and E under a high-speed stirrer (12000prm / min) according to step 3, and mixed with 25 parts of polyphenylene sulfide resin prepolymer (component C) in an open mill at 60-70°C for 30-40 minutes, and then hot-pressed into a 80x80x4mm substrate without Co 60 -γ irradiation can obtain ferrocene phthalocyanine cobalt-Cr / ceramic composite shrink wave substrate.

[0115] The magnetic permeability of the wave-shrinking substrate measured at 10.0 GHz is 2.0., the dielectric constant is 12.5, and the dielectric loss tangent tgδ≤2.0×10 -3 The copper-clad substrate made of 80×80×4mm can be used to make antennas with a frequency of 8.0-10.0GHz and a bandwidth of 13%. In contrast, antennas made of a similar American Rogers RO3010 dielectric substrate (dielectric constant 10) have a geometric size of 200x200x4mm and a bandwidth of only 5%. Therefore, the performance of the present invention is much better.

[0116] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A ferrocene metal phthalocyanine-metal complex / ceramic composite shrink wave substrate, characterized in that: The raw materials include by mass: Component A: 20-40 parts of ferrocene metal phthalocyanine-metal complex organic magnet containing Fe, Co, Ni coordinated by any one of Cu, Co, Ni, Mn, Cr ions; Component B: nanometer-level dielectric ceramic powder: 20 to 50 parts; Component C: thermosetting engineering plastic prepolymer or thermoplastic resin: 10-20 parts; Component D: flame retardant: 0.5-3.0 parts; Component E: surface modifier: 0.5-2.0 parts, And experienced Co 60 -γ irradiation dose is 0~300KGy.

2. The ferrocene metal phthalocyanine-metal complex / ceramic composite wave shrinkage substrate according to claim 1, characterized in that: The structural formula of component A is: Wherein M1 is any one of Fe, Co and Ni; R is methylene (CH2) n , n = 0, 1, 2, or 3; M2 is any one of chlorides, sulfates, acetates or nitrates of divalent metal ions Cu, Co, Ni, Mn or Cr.

3. The ferrocene metal phthalocyanine-metal complex / ceramic composite wave shrinkage substrate according to claim 1, characterized in that: The component B is any one or more of the rutile ceramic series in nano-scale high-frequency dielectric ceramics or the BaO-TiO2 ceramic series in nano-scale microwave dielectric ceramics.

4. The ferrocene metal phthalocyanine-metal complex / ceramic composite wave shrinkage substrate according to claim 1, characterized in that: The rutile ceramic series includes rutile titanium dioxide, calcium titanate, strontium titanate and zirconium titanate ceramic powders. The dielectric constant of the rutile titanium dioxide is 80-10, the dielectric constant of calcium titanate is 150-200, the dielectric constant of strontium titanate is 250-350, and the dielectric constant of zirconium titanate is 60; the dielectric constant of the BaO-TiO2 series ceramics is 600-800, and the particle size of the high-frequency dielectric ceramics and microwave dielectric ceramics is 50-300nm.

5. The ferrocene metal phthalocyanine-metal complex / ceramic composite wave shrinkage substrate according to claim 1, characterized in that: The component C is any one or more selected from cyanate resin, polyphenylene ether ketone, polyphenylene sulfide, prepolymer of bismaleimide resin as thermosetting engineering plastics, polyolefin, polyurethane, polyether, polycarbonate as thermoplastic resin.

6. The ferrocene metal phthalocyanine-metal complex / ceramic composite wave shrinkage substrate according to claim 1, characterized in that: The component D is any one selected from decabromodiphenyl ether, melamine, polyphosphate melamine, aromatic phosphites, diphosphites, phosphonates and phosphates.

7. The ferrocene metal phthalocyanine-metal complex / ceramic composite wave shrinkage substrate according to claim 1, characterized in that: The component E is any one selected from titanate coupling agent, silica coupling agent, aluminate coupling agent, cationic or anionic surfactant, dimethylsiloxane or dimethylsiloxane copolymer; or any one selected from organic modified polysiloxane, ureapropyl triethoxysilane, vinyl methyl dimethylsiloxane; or any one selected from oleic acid, acrylic acid and oleic acid in a 1:1 mixture.

8. The ferrocene metal phthalocyanine-metal complex / ceramic composite wave shrinkage substrate according to claim 1, characterized in that: The component A is obtained by the following synthesis reaction: Wherein M1 is any one of Fe, Co and Ni; Lewis acid is any one of BF3, AlCl3, NbCl5 or CF3NaSO3; R is methylene (CH2) n , n = 0, 1, 2, or 3; M2 is any one of chlorides, sulfates, acetates or nitrates of divalent metal ions Cu, Co, Ni, Mn or Cr.

9. The ferrocene metal phthalocyanine-metal complex / ceramic composite wave shrinkage substrate according to claim 8, characterized in that: In the synthesis reaction, the molar ratio of ferrocenylalkylamide to metal phthalocyanine diformyl chloride is (2.5-3.0):1.0, and the Lewis acid is any one of BF3, AlCl3, NbCl5 or CF3NaSO3.

10. The method for preparing the ferrocene metal phthalocyanine-metal complex / ceramic composite wave shrinkage substrate according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: first add anhydrous ethanol at 50-60° C. to the surface modifier, i.e. component E, to obtain an ethanol solution of the surface modifier; Step 2: Soak the ferrocene metal phthalocyanine-metal complex organic magnet, i.e. component A, the nano-scale dielectric ceramic powder, i.e. component B, and the flame retardant, i.e. component D, in the ethanol solution of the surface modifier for 30 minutes, filter the solution, wash away the residual ethanol on the surface modifier with acetone, and then dry the solution; Step 3: After fully mixing component A, component B, component D and component E under a high-speed stirrer, kneading with thermosetting engineering plastic prepolymer or thermoplastic resin, namely component C, in an open mill for 30 to 40 minutes under a certain temperature condition, and hot pressing or extruding into substrates of various specifications according to technical requirements, wherein the certain temperature refers to 130 to 150° C. for thermoplastic resin and 50 to 70° C. for thermosetting engineering resin prepolymer; Finally, use Co 60 -γ irradiation dose is 0~300KGy.

Citation Information

Patent Citations

  • Ferrocene bonding face to face diphthalocyanine complexes and uses thereof

    CN101328193A

  • Composite electromagnetic medium material containing dicyclopentadienyl iron phthalocyanine metal organic magnetic body and preparation method thereof

    CN101692366B